Patient and Family Preferences About Place of End-of-Life Care and Death: An Umbrella Review - Pinto, Sara (2024)
The place where people are cared towards the end of their life and die is a complex phenomenon, requiring a deeper understanding. Honoring preferences is critical for the delivery of high-quality care.